Purchase Determinants Of Customer Loyalty: The Mediating Effect Of E-Trust In E-Commerce - Lova, Anggil Nopra; Haryono, Gampo (Kirana Publisher (KNPub), 2023)
This study aims to find out and explain how the effect of e-service quality and website image on e-customer loyalty when online shopping is mediated by e-customer trust in e-commerce, both directly and indirectly. this research is quantitative. The sampling method used was purposive sampling with a research instrument in the form of a questionnaire which was distributed to 280 respondents who had used the e-commerce service. The results showed that the e-service quality and website image quality had a direct effect on e-customer trust and e-customer loyalty. E-trust has an important role in mediating the relationship between e-service quality and recovery service quality on e-customer loyalty. Therefore, an e-commerce must be able to make customers trusted by providing good e-service quality and good image in the event of a service failure by the company, learning from these findings we must maintain customer trust in terms of customer service so that these customers remain loyal and do not switch to competitors.